Survey Pengetahuan Masyarakat Tentang Terapi Komplementer - Saputra, Yoki (REAL in Nursing Journal, 2021)
Background: Complementary therapies that exist are one of the community's treatment options. Nurses can act as consultants to clients in choosing appropriate alternatives or help provide direct therapy. This survey aims to see a picture of public knowledge about complementary therapies. Methods: This study uses a descriptive analytic design to describe the public's knowledge about complementary therapy, which was conducted on 50 respondents using an online questionnaire. Result: The results obtained from 50 respondents 68% of respondents said they had known about complementary therapy and as many as 84% said they agreed if complementary therapy was combined with modern therapy. Conclusion: The development of complementary or alternative therapies has been extensive, including people who are involved in providing treatment because of the large number of health professionals and therapists involved in complementary therapies. Nurses as health professionals can participate in complementary therapy.Keywords: survey, knowledge, complementary therapy